IVC Filter Retrieval before and after Implementation of IVC Filter Retrieval Alert System (IFRAS): A Single-Center Experience - Hassan Aljaziri; Refaat Salman; Naila A. Shaheen; Mohammad Alaftan (The Arab Journal of Interventional Radiology)
Objective The aim of this study was to evaluate the effectiveness of the IVC filter retrieval alert system (IFRAS) in increasing the inferior vena cava (IVC) filter retrieval rate. Materials and Methods This study was a case-based retrospective study, for patients who had IVC filter insertion from January 2013 to December 2019 with a sample of 756 patients. The sample was divided into two groups for filter retrieval rate: before the implementation of the tracking system (IFRAS) between 2013 and 2015 with a sample of 321 patients, and after the implementation of the tracking system (IFRAS) between 2016 and 2019 with a sample of 435 patients. This study aimed to compare the IVC filter retrieval rate before and after the implementation of the IFRAS. The tracking system (IFRAS) protocol was applied by a dedicated employee who is actively tracking patients and strictly following them up with a referred physician or interventional radiologist through the interventional radiology clinic. Results The IVC filter retrieval before the implementation of the tracking system (2013–2015) was 38.3% (123/321), and it became 54.25% (236/435) after the implementation of the tracking system with a p-value less than 0.001. Before implementing the tracking system, patients with no follow-up after IVC filter insertion were 45.17% (145/321), and this decreased to 41.15% (179/435) after implementing the tracking system. Conclusion The study proved a statistically significant difference in increasing the IVC filter retrieval rate after implementing the IFRAS.